Ethical leadership in schools : creating community in an environment of accountability - Strike, Kenneth A. (Corwin Press, 2007)
In an age of accountability and transparency, headteachers are held responsible for everything from results to school finances. Because of this increased accountability, school leaders must regularly confront difficult ethical dilemmas.